What kind of late effects of antineoplastic treatment can we meet in children treated for neoplastic disease? - Stefanowicz, Joanna; Stachowicz-Stencel, Teresa; Sierota, Danuta; Adamkiewicz-Drożyńska, Elżbieta; Bień, Ewa; Połczyńska, Katarzyna; Szołkiewicz, Anna; Synakiewicz, Anna; Birkholz, Dorota; Balcerska, Anna (Contemporary Oncology/Współczesna Onkologia, 2009)
The five-year survival rate for children suffering from neoplastic disease is currently 80-85%. Thus, the number of children cured of neoplasms is still increasing. Aim of the study: Analysis of prevalence of long-term consequences of disease and antineoplastic treatment. Material and methods: The study group consisted of 10 children who were treated for neuroblastoma (NBL) and soft tissue sarcomas (STS) at the Department of Paediatrics, Haematology, Oncology and Endocrinology, Medical University of Gdansk, between 1992 and 2004. All patients had complete physical and laryngological examination. The basic biochemical tests in blood and urea were performed and the level of sex hormones determined for every patient. ECG, echocardiography, ultrasonography of the abdomen, audiogram and three times repeated blood pressure taking was made in order to exclude arterial hypertension. Results: The following abnormalities were observed: neurological (flaccid paresis of lower limbs) (2 patients), nephrological (state after urinary bladder resection and operation of ureter implantation into ileal conduit and ureterocutaneostomy) (1), ophthalmic (post enucleation state), endocrine (somatotropic hypopituitarism) (1), laryngological (sensorineural hypoacusis at high frequencies) (2), chronic hepatitis type C (1), type B (2), vascular: stenosis of inferior vein (complication after nephrectomy). Moreover, haemodynamic insignificant cardiac defects in the form of mitral insufficiency (2) and tricuspid insufficiency (2) were diagnosed. Conclusions: Patients who completed the antineoplastic treatment need routine control tests and regular secondary medical care to ensure early detection and monitor long-term consequences of both disease and treatment.